Strategic directions and prerequisites for the development of integrated structures in investment and construction activities - S. I. Beliakov (Vestnik MGSU)
Introduction. In conditions of high dynamics of changes in the external environment, the key problem of managing integrated structures of investment and construction activities is the development of effective solutions in the field of strategic development and long-term optimization. Within the framework of the study of this topical issue, it is advisable to consider the directions of strategic development of integrated structures on the basis of scenario-factor analysis.Materials and methods. Economic modeling of the target function of the strategic development of the integrated structure of investment and construction activities, formalized in various indicators depending on strategic priorities and business model of the organization, is carried out on the basis of application of tools of factor and regression analysis based on expert assessments and a representative statistical sample over the past periods based on data on the practice of functioning of large integrated structures of investment and construction activities.Results. Main results of the research include the systematization of alternative approaches to improving the efficiency of integrated structures of investment and construction activities used in the development and implementation of strategic management tasks for their development, the author’s classification of the factor space of strategic development of integrated structures of investment and construction activities and development scenarios of investment and construction associations based on a system of criteria and their corresponding typical situations, a formalized functional model of the target indicator of the level of strategic development of the integrated structure of investment and construction activities.Conclusions. The results of the scenario-factor analysis and the development of the target functional model form the scientific and methodological basis and prerequisites for the development and application of approaches to modelling the strategic development of integrated structures of investment and construction activities. Further scientific research in the subject area under consideration can be carried out in a number of areas, the priority of which the author presents the development and justification of methodological approaches and tools for the formation of production programmes for strategic development based on the synchronization of investment and production potentials within the framework of business models of investment and construction activities.